Chasing Animals With Split Attention: Are Animals Prioritized in Visual Tracking?. (August 2018) - Hagen, Thomas; Espeseth, Thomas; Laeng, Bruno
Some evolutionary psychologists have hypothesized that animals have priority in human attention. That is, they should be detected and selected more efficiently than other types of objects, especially man-made ones. Such a priority mechanism should automatically deploy more attentional resources and dynamic monitoring toward animal stimuli than nonanimals. Consequently, we postulated that variations of the multiple object or identity tracking and multiple event monitoring tasks should be particularly suitable paradigms for addressing the animate monitoring hypothesis, given their dynamic properties and dependency on divided attention. We used images of animals and artifacts and found neither a substantial sign of improvement in tracking the positions associated with animal stimuli nor a significant distracting effect of animals. We also failed to observe a significant prioritization in orders of response for positions associated with animals. While we observed an advantage for animals in event monitoring, this appeared to be dependent on properties of the task, as confirmed in further experiments. Moreover, we observed a small but inconclusive advantage for animals in identity accuracy. Thus, under certain conditions, some bias toward animals could be observed, but the evidence was weak and inconclusive. To conclude, effect sizes were generally small and not conclusively in favor of the expected attentional bias for animals. We found moderate to strong evidence that images of animals do not improve positional tracking, do not act as more effective distractors, are not selected prior to artifacts in the response phase, and are not easier to monitor for changes in size.